Design of 3D Hybrid Composite Scaffolds: Effect of Composition on Scaffold Structure and Cell Proliferation. Issue 1 (December 2013) - Dorati, R.; Colonna, C.; Tomasi, C.; Genta, I.; Modena, T.; Conti, B.; Lendlein, Andreas; Neffe, Axel T.
Summary The aim of this study was to develop multi‐phase composite 3D scaffolds and to investigate the in vitro degradation performance, the cell seeding capacity and cells proliferation onto/into the composite scaffolds. Multi‐phase composite scaffolds were formulated by solvent casting and particulate leaching technique, hydroxyapatite (HAP) was used to improve the mechanical properties of poly[(DL‐lactide)‐coglycolide] (PLGA) polymer scaffold, while chitosan (CTS) was added to the formulation for its bioactivity, osteoconductivity and bioadhesive properties. The in vitro degradation results demonstrated that the composite scaffold had a degradation rate correlating with their composition and structural features. Adult fibroblast cells were seeded on the surface of the composite scaffolds. Cell viability and long‐term proliferation onto/into composite scaffolds were evaluated. The results showed that viable cells attached on the surface of scaffolds gradually migrated into the porous scaffold. These results suggest that the two‐phase scaffold, namely PLGA/HAP and PLGA/CTS composite scaffolds, are promising grafts for bone tissue engineering. Further studies are in progress to design an improved three‐phase composite construct obtained combining PLGA, HAP and CTS in a wafer‐like scaffold.